A novel thermoplastic sizing containing graphene oxide functionalized with structural analogs of matrix for improving interfacial adhesion of CF/PES composites. (November 2018) - Liu, Liu; Yan, Fei; Li, Ming; Zhang, Mengjie; Xiao, Linghan; Shang, Lei; Ao, Yuhui
Abstract: A novel complex sizing containing PES and functionalized GO was prepared for improving interfacial adhesion of CF/PES composites. To achieve better dispersion of GO in sizing and improve the interfacial compatibility of composites, GO were covalently functionalized by 4, 4′-diaminodiphenyl sulfone (DDS) and 4, 4′-diaminodiphenyl ether, which have similar chemical structures to PES matrix. SEM, dynamic contact angle and TGA tests showed that functionalized GO were closely attached to the CF surface, and the surface energy as well as the thermal stability of CF were greatly increased. Among all the sizings, PES/GO-DDS exhibited the best reinforcing effect, revealing a significant increase of 74.1% in IFSS and 40.1% in ILSS as compared with un-sized CF. Notably, the variation trend of mechanical properties was accordant with the interfacial strength. Moreover, the interface enhancement mechanisms were proposed, the increased interfacial adhesion was benefited from the positive effect of interface layer.